2020
DOI: 10.1111/jcpe.13227
|View full text |Cite
|
Sign up to set email alerts
|

Gingival tissue human beta‐defensin levels in relation to infection and inflammation

Abstract: Aim To profile gingival tissue levels of human beta‐defensin (hBD)‐2 and hBD‐3 in relation to gingival inflammation, Th17‐related cytokine concentrations, Porphyromonas gingivalis counts, and gingipain and total protease activities. Materials and Methods Gingival tissue and subgingival plaque samples were collected from 21 periodontitis patients including 48 periodontal pocket sites with marginal, mild, or moderate to severe inflammation. hBD levels were determined by immunodetection, P. gingivalis counts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“… 26 HBD has been found to be closely associated with inflammation, 24 and upregulation of HBD has been observed during infection and inflammation. 27 In agreement with previous studies, the GO annotations related to HBD are oxygen transport, iron ion binding, blood coagulation and combination with oxygen. 28 Sickle cell disease (SCD) and β‐thalassemia are the two most prevalent β‐haemoglobinopathies worldwide.…”
Section: Discussionsupporting
confidence: 91%
“… 26 HBD has been found to be closely associated with inflammation, 24 and upregulation of HBD has been observed during infection and inflammation. 27 In agreement with previous studies, the GO annotations related to HBD are oxygen transport, iron ion binding, blood coagulation and combination with oxygen. 28 Sickle cell disease (SCD) and β‐thalassemia are the two most prevalent β‐haemoglobinopathies worldwide.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the functional features of CIDEA may partially explain the weakening of pelvic oor muscle tissue in POP. A previous study found that HBD was closely associated with in ammation, and upregulation of HBD was observed during infection and in ammation [14] . Recent studies have revealed that immunoregulatory and in ammatory processes play a crucial role in repairing the extracellular matrix after pelvic oor muscle injuries resulting from pregnancy and childbirth [15] Thus, this study shows that cell apoptosis and in ammation are important factors in the development and progression of recurrent POP.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, our model did not involve bacteria. Bacteria can modulate antimicrobial peptide gene expression and degrade antimicrobial peptides that are expressed by keratinocytes [22]. In vitro studies have shown that 2 -FL and 3-FL alter the adhesion and growth of various bacteria [23][24][25], necessitating an examination of the cellular responses that are induced by these HMOs in an organotypic mucosa-bacterial biofilm culture model.…”
Section: Discussionmentioning
confidence: 99%